2021
DOI: 10.1186/s13195-021-00881-w
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial alpha and gamma oscillations scale with the severity of cognitive dysfunction in patients on the Alzheimer’s disease spectrum

Abstract: Background Entrainment of neural oscillations in occipital cortices by external rhythmic visual stimuli has been proposed as a novel therapy for patients with Alzheimer’s disease (AD). Despite this increased interest in visual neural oscillations in AD, little is known regarding their role in AD-related cognitive impairment and in particular during visuospatial processing. Methods We used source-imaged magnetoencephalography (MEG) and an establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…One prior MEG study reported aberrant theta and stronger baseline alpha activity in the prefrontal cortices of participants with HAND, which distinguished cognitively impaired from unimpaired PWH and controls [ 29 ]. Other studies of attention processing in patients on the AD spectrum revealed decreased theta [ 39 , 40 ] and alpha [ 30 , 31 ] responses during attention and visuospatial processing. Thus, while the current findings are novel, the overlap in aberrant attention-related oscillatory activity in each frequency band across frontoparietal hubs in the ADS and HAND groups relative to controls is not entirely surprising.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…One prior MEG study reported aberrant theta and stronger baseline alpha activity in the prefrontal cortices of participants with HAND, which distinguished cognitively impaired from unimpaired PWH and controls [ 29 ]. Other studies of attention processing in patients on the AD spectrum revealed decreased theta [ 39 , 40 ] and alpha [ 30 , 31 ] responses during attention and visuospatial processing. Thus, while the current findings are novel, the overlap in aberrant attention-related oscillatory activity in each frequency band across frontoparietal hubs in the ADS and HAND groups relative to controls is not entirely surprising.…”
Section: Discussionmentioning
confidence: 98%
“…Beyond the general differences between patients and controls, we found disease-specific theta alterations in several brain regions including the prefrontal, parietal, occipital, and temporal cortices. Theta aberrations have been highlighted in previous studies as markers of cognitive impairment separately in AD and HAND [ 27 , 29 , 40 , 44 , 45 ]. These disease-specific differences in theta oscillatory activity may suggest more fine-scale neurophysiological differences in temporal segmentation and higher order allocation of attentional resources, which could be secondary to regional amyloid accumulation in those on the ADS relative to HAND, as multiple studies have shown normal amyloid levels in patients with HAND [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MEG and MRI data processing closely followed previously reported pipelines [11,12,64,65]. The structural MRI data were aligned parallel to the anterior and posterior commissures and transformed into standardized space.…”
Section: Meg and Mri Processingmentioning
confidence: 99%
“…Gamma oscillations were first discovered by Adrian (4) who reported that the oscillations were induced by odorous substances. Since, studies have demonstrated that they could be induced by other stimuli and be presented in various structures in the human brain, with different functional connections, such as learning, sensory, consciousness, and motor functions (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%